2011
DOI: 10.1016/j.jpain.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pain, Gender, and Age on Sleep/Wake and Circadian Rhythm Parameters in Oncology Patients at the Initiation of Radiation Therapy

Abstract: To date, no studies have evaluated for differences in subjective and objective measures of sleep disturbance in oncology outpatients with and without pain. This descriptive study recruited 182 patients from two radiation therapy (RT) departments at the time of the patient's simulation visit. Approximately 38% of the sample reported moderate to severe pain (i.e., worst pain intensity of 6.2 ± 2.4). After controlling for age, patients with pain reported worse sleep quality and more sleep disturbance using the Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 65 publications
1
14
0
2
Order By: Relevance
“…The number of participants in the control groups (including cancer and noncancer) evaluated in studies was 1607. Only 90 studies (35%) included a comparison group in the study design, with most comparison groups being subjects with cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of participants in the control groups (including cancer and noncancer) evaluated in studies was 1607. Only 90 studies (35%) included a comparison group in the study design, with most comparison groups being subjects with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…When selecting participants for studies, potentially important inclusion and exclusion criteria for sleep were rarely addressed. For example, only 19.7% ( n = 50) of the studies reviewed excluded for previous sleep disorder or current treatment of sleep disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Since these patients were evaluated prior to receiving their next dose of CTX, these between group differences suggest that CP is associated with increases in morning fatigue. Since pain is known to disrupt sleep, 17 these relatively high levels of morning fatigue may be related to the higher levels of both pain and sleep disturbance reported by these patients.…”
Section: Discussionmentioning
confidence: 97%
“…Neuropathic pain can be associated with insomnia symptoms (Smith and Haythornthwaite, 2004). Previous studies have indicated a reciprocal association between chronic pain and sleep disturbance in various medical conditions, such as cancers, angina, renal failure, fibromyalgia, arthritis and musculoskeletal strains (Buffum et al, 2011;Edinger et al, 2005;Wilson et al, 1998). Increased daytime pain has been associated with poor night-time sleep and poor sleep is associated, in turn, with augmented next-day pain.…”
Section: Discussionmentioning
confidence: 99%